Molecular Factors and Pathways of Hepatotoxicity Associated with HIV/SARS-CoV-2 Protease Inhibitors - Ji, Cheng (International journal of molecular sciences, 2023)
Antiviral protease inhibitors are peptidomimetic molecules that block the active catalytic center of viral proteases and, thereby, prevent the cleavage of viral polyprotein precursors into maturation. They continue to be a key class of antiviral drugs that can be used either as boosters for other classes of antivirals or as major components of current regimens in therapies for the treatment of infections with human immunodeficiency virus (HIV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, sustained/lifelong treatment with the drugs or drugs combined with other substance(s) often leads to severe hepatic side effects such as lipid abnormalities, insulin resistance, and hepatotoxicity. The underlying pathogenic mechanisms are not fully known and are under continuous investigation. This review focuses on the general as well as specific molecular mechanisms of the protease inhibitor-induced hepatotoxicity involving transporter proteins, apolipoprotein B, cytochrome P450 isozymes, insulin-receptor substrate 1, Akt/PKB signaling, lipogenic factors, UDP-glucuronosyltransferase, pregnane X receptor, hepatocyte nuclear factor 4α, reactive oxygen species, inflammatory cytokines, off-target proteases, and small GTPase Rab proteins related to ER-Golgi trafficking, organelle stress, and liver injury. Potential pharmaceutical/therapeutic solutions to antiviral drug-induced hepatic side effects are also discussed.